Synthesis and characterization of a random terpolymer of L-lactide, ε-caprolactone and glycolide - Srisa-ard M. (2014)
A random terpolymer of L-lactide (LL),ε-caprolactone (CL) and glycolide (G) has been synthesized in bulk at 130°C using stannous octoate as the coordination-insertion initiator. The terpolymer, poly(LL-ran-CL-ran-G), has been characterized by a combination of analytical techniques: GPC, 1HNMR, 13CNMR, DSC and TG. Molecular weight characterization by GPC shows a unimodal molecular weight distribution with values of Mn=1.01 x 105 g mol-1 and MwIMn=2.17. Compositional and microstructural analysis by 1HNMR and 13CNMR, respectively, reveal a terpolymer composition of LL:CL:G=74:15:11 (mol%) with a chain microstructure consistent with random monomer sequencing. This latter view is supported by the terpolymer temperature transitions (Tg and Tm) from DSC and the thermal decomposition profile from TG. The results and, in particular, the conclusion that it is a random rather than a statistical terpolymer are discussed in the light of current theories regarding the mechanism of this type of polymerization. © 2001 Society of Chemical Industry.